2015
DOI: 10.1109/tps.2014.2367538
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mechanical Probes for Evaluation of Plasma Acceleration in Ablative PPT

Abstract: In pulsed plasma thrusters (PPTs), a highly ionized plasma is created and accelerated by means of a pulsed triggered vacuum gap discharge with concurrently occurring ablation, ionization, and Lorentz-force-based acceleration of propellant. The plasma flow behavior during the PPT discharge is, therefore, highly dependent on time, space, and operation parameters. Experimental work is seen as the necessary key to further understand the processes involved and to determine future research needs. The application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This is the reason that we can observe some weak shockwaves in the plasma beams of EP thrusters. It has been reported that a plasma bowshock is formed in front of a probe during the ignition of a pulsed plasma thruster (PPT) [23]. PPTs are typical EP thrusters that operate in a vacuum environment.…”
Section: Introductionmentioning
confidence: 99%
“…This is the reason that we can observe some weak shockwaves in the plasma beams of EP thrusters. It has been reported that a plasma bowshock is formed in front of a probe during the ignition of a pulsed plasma thruster (PPT) [23]. PPTs are typical EP thrusters that operate in a vacuum environment.…”
Section: Introductionmentioning
confidence: 99%
“…The PPT employed in microsatellites is usually equipped with a spark plug. A high voltage is applied to the electrodes and the spark plug is used to initiate discharge by providing a large supply of free electrons to start an avalanche in the discharge gap between the electrodes [5][6][7][8]. The operation of the spark plug needs an independent power supply, thus increasing the volume, mass and structural complexity of the thruster.…”
Section: Introductionmentioning
confidence: 99%